Analysis of Political Cartoon in Jakarta Post E-Paper - Yan Reiza Permana (Universitas Pendidikan Mandalika, 2020)
This study was concerned on the way the author explores the hidden meaning and message in semiotics signification of President Jokowi cartoons in Jakarta Post e-paper. The writer focused on five cartoons of President Jokowi published by Jakarta Post e-paper and wanted to know about the hidden meaning and message that tried to convey by the Jakarta Post e-paper. Furthermore, this research covered an interdisciplinary study that scopes semiotics and Critical Discourse Analysis (CDA, in which the researcher tried to unhook the messages and explain the linguistic means of that construct the hidden message and ideology of the cartoons. In conducting the research, the researcher used Peirce's semiotic and Van Dijk's ideological square model. The researcher used purposive sampling in taking data. The total of the data analyzed was five cartoons. From the analysis, the message conveyed in the first cartoon criticizes to President Jokowi’s decision which is rated as indifference. The second cartoon also criticizes President Jokowi rated as pretend to against china's exploration. Furthermore, the third cartoon criticizes President Jokowi controlled by some political parties. Meanwhile, the fourth cartoon criticizes President Jokowi as a President uneasily defeated in a political term, but ignoring the humanity, and the last cartoon criticizes about President Jokowi and Prabowo similarities with previous President in terms of attitudes. The researcher also got the linguistic as means of used to convey the message such as the choice of a figure of speech.